Large Polarization and Susceptibilities in Artificial Morphotropic Phase Boundary PbZr1−xTixO3 Superlattices. (22nd January 2020) - Lupi, Eduardo; Ghosh, Anirban; Saremi, Sahar; Hsu, Shang‐Lin; Pandya, Shishir; Velarde, Gabriel; Fernandez, Abel; Ramesh, Ramamoorthy; Martin, Lane W.
Abstract: The ability to produce atomically precise, artificial oxide heterostructures allows for the possibility of producing exotic phases and enhanced susceptibilities not found in parent materials. Typical ferroelectric materials either exhibit large saturation polarization away from a phase boundary or large dielectric susceptibility near a phase boundary. Both large ferroelectric polarization and dielectric permittivity are attained wherein fully epitaxial (PbZr0.8 Ti0.2 O3 ) n /(PbZr0.4 Ti0.6 O3 )2 n ( n = 2, 4, 6, 8, 16 unit cells) superlattices are produced such that the overall film chemistry is at the morphotropic phase boundary, but constitutive layers are not. Long‐ ( n ≥ 6) and short‐period ( n = 2) superlattices reveal large ferroelectric saturation polarization ( P s = 64 µC cm −2 ) and small dielectric permittivity (εr ≈ 400 at 10 kHz). Intermediate‐period ( n = 4) superlattices, however, exhibit both large ferroelectric saturation polarization ( P s = 64 µC cm −2 ) and dielectric permittivity (εr = 776 at 10 kHz). First‐order reversal curve analysis reveals the presence of switching distributions for each parent layer and a third, interfacial layer wherein superlattice periodicity modulates the volume fraction of each switching distribution and thus the overall material response. This reveals that deterministic creation of artificial superlattices is an effective pathway for designing materials with enhanced responses to applied bias. Abstract : Simultaneous large susceptibility and polarization in the PbZr1− x Ti x O3 system is observed as a function of superlattice periodicity utilizing unit‐cell precise pulsed‐laser deposition. (PbZr0.8 Ti0.2 O3 ) n /(PbZr0.4 Ti0.6 O3 )2 n superlattices exhibit a large volume fraction of morphotropic phase‐boundary‐like character at the interfaces, which enables large permittivity while remnant parent phases maintain large polarization.